Potential of bromelain from Ananas comosus (L.) Merr. as an irrigation material for dental root canals - Nadia Ayesha Salsabila; Laksmi Aristha Bhanuwati; Fidela Desfitria Zahra; Wigya Aulia Nastiti; Alma Aura Iryandari; Intan Puspita; Juni Handajani (Faculty of Dentistry, Universitas Gadjah Mada, 2026)
Dental caries remains a significant oral health problem worldwide, with untreated cases potentially causing pulp damage that requires endodontic treatment. Sodium hypochlorite (NaOCl), the most commonly used root canal irrigant, can be toxic to pulp cells. This study evaluated bromelain enzyme from pineapple core (Ananas comosus (L.) Merr.) as an alternative irrigant with high antibacterial activity and low toxicity. Bromelain concentrations of 20%, 30%, 40%, and 50% were tested for their effects on pulp cell viability, confluence, and antibiofilm activity againstEnterococcus faecalis. Results showed that 50% bromelain maintained high pulp cell viability and confluence while inhibiting 70% of E. faecalis biofilm formation (p < 0.05). These findings suggest that bromelain extract from pineapple core has potential as a root canal irrigant, but further in vivo studies and formulation optimization are needed before clinical application.